Influence of α-tocopherol on physicochemical properties of chitosan-based films - Martins, Joana (2012)
tosan has been exploited as a material for the development of edible films, and additionally can be used as a carrier of functional compounds such as α-tocopherol. The aim of this work was to evaluate the effects of the incorporation of α-tocopherol in chitosan-based films. FTIR and thermal analyses were performed and showed that the incorporation of α-tocopherol affects the chemical structure of chitosan-based films with the establishment of new chemical bonds and the decrease of crystallinity. Results also showed that the increase of α-tocopherol concentration promotes a decrease of water content (from 12.6 to 11.4%) of the films. The addition of α-tocopherol to chitosan films leads to a significant reduction (p < 0.05) of tensile strength from 34.06 to 16.24 MPa, and elongation-at-break from 53.84 to 23.12%. Film opacity values (ranging from 4.74 to 7.83%) increased when α-tocopherol was incorporated into the film. Antioxidant capacity of chitosan-based films was evaluated and was enhanced when α-tocopherol was present in the film matrix. Results showed that α-tocopherol can be successfully added to the chitosan films enhancing the final quality and shelf-life extension of food products.